Electronic Module-Based Learning Media Training for Teachers in Kertamukti Village - Sugendi, Agus; Badar, Alfi Munajab; Ramadhan, Alif; Permadi, Aulia; Komala, Driska; Nurhayati, Epi; Trinalia, Fadilla; Fikri, Fauzia Nurul; Namah, Indah Tamimun; Haidar, Mohammad Zidan; Nur Fadillah, Nanda Aulya; Wulandari, Neng; Rinda, Silfia; Agustin, Yunika Dwi; Imaduddin, Aam (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The minimal use of instructional media in schools in Kertamukti Village is caused by the low competence of teachers in the use of information technology that supports learning. The purpose of the electronic module participatory training is to increase the competence of teachers in compiling and presenting interactive and innovative electronic learning media, so that it is expected to be able to attract the attention and interest of students to increase learning motivation. This training involved teachers at schools in Kertamukti Village, Cimerak District, Pangandaran Regency. This electronic module-based learning media training was attended by 9 teachers from several schools, namely: SD Negeri 1 Kertamukti 3 people, SD Negeri 3 Kertamukti 2 people, MI Cireuma 2 people, and One Roof Middle School 1 Cimerak 2 people. This training uses a participatory method designed to actively involve all activity participants. The training activities are divided into three stages, namely examining the theoretical concepts of electronic modules, simulations and practice, independent learning to develop electronic modules. The teachers participated in 8 hours of training materials and 24 hours of assignments to make electronic modules at their respective homes, so a total of 32 hours of training with teachers producing products in the form of electronic modules that can be used in their respective schools